The South Texas Health Status Review : A Health Disparities Roadmap. - Ramirez, Amelie G. (Springer International Publishing AG, 2013)
This book is a roadmap of the disparities that burden the health of South Texas residents, especially Hispanics, compared to the rest of Texas and nation. Surveys more than 35 health indicators from cancers to diabetes to HIV/AIDS to maternal health and more.